Socio-technical networks science and engineering design - Hu, Fei.; Mostashari, Ali.; Xie, Jiang. (CRC Press, 2010)
"While there are some sporadic journal articles on socio-technical networks, readers need an integrated resource discussing the STN design. This book provides a complete introduction to the fundamentals of socio-technical networks, including its definition, historical background, and significance. The authors provide basic network architecture from the OSI model perspective and address some challenging design issues. The text also covers all major network protocol design in a typical STN and the application of wireless networks such as sensor networks, WiMAX, etc. in STN access. The book presents STN case studies from healthcare, virtual communities"--